2022
DOI: 10.1007/s42773-022-00150-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the simultaneous adsorption mechanism of ammonium and phosphate on magnesium-modified biochar and the slow release effect of fertiliser

Abstract: To decrease the eutrophication caused by nitrogen (N) and phosphorus (P) in water, magnesium-modified corn stalk biochar (MgB) was prepared under the synergistic impact of the multi-pyrolysis temperatures and Mg2+ contents for the co-adsorption of ammonium (NH4+-N) and phosphate (PO43−). The co-adsorption mechanism, slow-release performance and plant application of MgB were systematically studied. The results showed that pyrolysis temperatures (350–650 °C) and Mg2+(0–3.6 g/L) contents not only altered the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The core of the adsorption process is the adsorbent, which impacts adsorption performance in four aspects: adsorption capacity, adsorption selectivity, adsorption/desorption rate, and regeneration . Many adsorbents have been reported, such as mesoporous materials, carbon nanotubes, biochar, hydrogels, CeO 2 particles, and graphene . These adsorbents were used on a laboratory scale; however, there still exist some problems during the industrial application that need to be resolved immediately, such as the high cost, complex synthetic route, and difficulty in recycling.…”
Section: Introductionmentioning
confidence: 99%
“…The core of the adsorption process is the adsorbent, which impacts adsorption performance in four aspects: adsorption capacity, adsorption selectivity, adsorption/desorption rate, and regeneration . Many adsorbents have been reported, such as mesoporous materials, carbon nanotubes, biochar, hydrogels, CeO 2 particles, and graphene . These adsorbents were used on a laboratory scale; however, there still exist some problems during the industrial application that need to be resolved immediately, such as the high cost, complex synthetic route, and difficulty in recycling.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient release performance from biochar was related to ion binding capacity and absorption level [16]. Therefore, in addition to optimizing the biochar application rate, biochar modification for absorption capacity and strength has become an inevitable trend to enhance its slow-release effect [107]. Commonly used methods include chemical and physical modifications, with chemical modification being the most extensively employed method.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional urea and NH 4 Cl, N from biochar‐embedded fertilizers was released at a significantly slower rate ( p < .05) during the incubation period, allowing more N to be retained in the fertilized soil to sustain plant N consumption for longer, as supported by Kim et al (2014) and Sun et al (2017) who reported that a biochar‐urea composite compared with chemical urea delayed N release and a wide ammonium‐nitrate ratio can be maintained over a longer period of time. We observed that N fertilizers may allow water to seep into biochar pores, causing osmotic pressure to build up, allowing BSRNF granules to break apart and further release urea and NH 4 Cl as any urea or NH 4 Cl found on the exposed surfaces of SRF pellets will be rapidly dissolved when exposed to water after being released into the soil (He et al, 2022).…”
Section: Discussionmentioning
confidence: 99%